(untitled) (Journal of the College of Basic Education, 2022)
The Students’ Foundation is a religious-political institution that gained great importance in the Almohad state, which was formed thanks to the advocates of this institution, which adopted the ideas of its founder, Muhammad bin Tumart, and after him, Abd al-Mu’min bin Ali, who gave it importance in order to establish a mature, educated party whose members owe allegiance and obedience to his person and his state. To seek help from them and to follow his orders, so he delegates them to carry out cultural, administrative and military tasks, as the curricula of this institution were not limited to religious sciences only, but rather expanded to include all Arab sciences and their literature, as well as mathematical and military sciences. The Almohad caliphs for the purpose of improving the living conditions of its members by offering them free grants and securing suitable job opportunities for each of them according to his personal capabilities and capabilities,